Temporal change in eruption style during the basaltic explosive An’ei eruption of the Izu-Oshima volcano, Japan: insights from stratigraphy and chemical composition analyses - Ikenaga, Yuya; Maeno, Fukashi; Yasuda, Atsushi (Frontiers in Earth Science, 2023)
Basaltic eruptions sometimes show an explosive and complex nature; thus, clarifying the sequence and controlling parameters is essential for understanding their causes. The An’ei eruption of the Izu-Oshima volcano during 1777–1792 was a complex basaltic eruption producing lava flows, pyroclastic falls, and ash plumes. We reconstructed the transition of the eruption style based on geological data combined with comparisons with data from historical documents and used chemical analyses to develop a magma plumbing model. The An’ei eruption started in August 1777 with scoria ejection. The scoria deposit was classified into Units A–C. Unit A scoria was produced by early weak explosions and more intense subsequent explosions. Unit B scoria marked a return to weak plumes before the summit eruption reached its climactic phase in November 1778 and explosively ejected Unit C scoria. Several lava flows were also effused from the foot of the scoria cone during these periods of scoria ejection. After a 5-year hiatus, the eruption ultimately shifted to persistent, weak ash ejection and pyroclastic surges. The tephra volumes of Units A, B, and C were estimated at 1.9–4.3 × 107, 0.6–4.5 × 106, and 1.3–3.2 × 107 m3, respectively. Associated column heights of 8–11, 3–10, and 9–12 km were obtained for Units A, B, and C, respectively, resulting in sub-Plinian classification. Chemical analyses have shown that the plagioclase phenocryst content increased as the eruption progressed. The transition from relatively weak activity with Strombolian and sub-Plinian explosions, caused by aphyric magma, to short-period activity with more intense sub-Plinian explosions, caused by porphyritic magma, can be explained by evacuation of magma from multiple reservoirs with different contents of plagioclase phenocrysts. Simultaneous lava flows that have different petrological features from those of the scoria eruptions also suggest multiple magma reservoirs and pathways. This view of the temporal change in eruptive style, corresponding to change in magma type, is essential for understanding the eruptive processes of large-scale basaltic eruptions of the Izu-Oshima volcano and contributes to clarifying the nature and hazards of basaltic eruptions which turn into explosive activities in general.